Letter to Jan Else signed by Antigone Kotsiopulos and Ginny Webster - Kotsiopulos, Antigone, author; Webster, Ginny, author (Colorado State University. Libraries, 1992)
Thank you letter to Friends of the Gustafson Gallery member and department faculty member, Janet J. Else, signed by Department Head, Antigone Kotsiopulos, and Friends of the Gustafson Gallery President, Ginny (Virginia) Webster.
Keywords: Fashion -- History; Fashion -- Exhibitions